Liver clear cell foci and viral infection are associated with non-cirrhotic, non-fibrolamellar hepatocellular carcinoma in young patients from South America - Cano, L (2018)
We previously described a divergent clinical and molecular presentation of hepatocellular carcinoma (HCC) in Peru. The present study aimed to further characterize the tissue features associated with this singular nosological form of HCC in order to gain insight into the natural history of the disease. We performed an exploratory analysis of the histology of both tumor and non-tumor liver (NTL) tissues from 50 Peruvian HCC patients, and compared with that of 75 individuals with non-HCC liver tumor or benign liver lesions as a baseline for NTL features. We complemented this approach with a transcriptome analysis in a subset of NTL tissue samples and also performed an ultra-sensitive hepatitis B virus (HBV) detection in liver tissues of the patients. Overall, results highlighted the low rate of liver parenchymal alterations in a young patient cohort (median age: 40 years old), despite a strong prevalence of underlying HBV infection (c. 67%). Withal, liver clear cell foci of cellular alteration were genuinely associated with HCC and appended to some changes in immune and G protein-coupled receptor gene expression ontologies. Our findings confirm the occurrence of a particular setting of HCC in South America, a region where the pathophysiology of liver cancer remains largely unexplored.